THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, MANAGERIAL OWNERSHIP AND INTELLECTUAL CAPITAL ON COMPANY VALUE WITH COMPANY PERFORMANCE AS A MEDIATION VARIABLE - Suwandi, Suwandi; Susilawati, Agnes Dwita (LPPM STIE Muhammadiah Bandung, 2023)
Company performance in this study use as the mediating variable to examine how managerial ownership, intellectual capital, and companyperformance affect firm value. 47 mining businesses listed on the IDX between 2017–2021 constitute the study population using a sample selection method called purposive sampling. 36 mining companies were sampled for this study. This study used simple regression as a data analysis method using SPSS ver.26 software. Intellectual capital isn’ta factor that affects the company value. There is no difference that affects company value in company performance. Managerial ownership variables significantly and profitably influence business performance. Through the use of corporate performance variables, corporate social responsibility and corporate values can be linked. Company performance indicators can act as mediators between managerial ownership and firm value. Variables related to business performance cannot act as mediators in the relationship between intellectual capital and firm value.